HAKIKAT MANUSIA DALAM AL-QURAN - Masrohan, Masrohan (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractThe Qur'an is the Book of Allah revealed to the Prophet Muhammad to allmen. In it God greets sense and human feelings, teaches monotheism to man, toÂ purify man with a variety of worship, showing man the things that can bringgood and welfare of the individual and social life of man, guiding people to thereligion of the sublime that manifest themselves, develop personality humans, asÂ well as increasing the level of human beings to human perfection. Thus, mancan realize the happiness in the world and the hereafter. The Qur'an alsoencourages people to reflect about himself, the wonders of creation and theaccuracy of its creation. Therefore, the introduction of man against himself candeliver to ma'rifatillah The Qur'an also contains clues about human nature andthe nature of the psychological state associated with the formation of a truepicture of human personality, the main motivation that drives human behavior,and the factors which underlying harmony and perfection of the humanpersonality and the realization of human mental health.Keywoard: hakikat, manusia, al-Qurâ€™an, insÄn, al-nÄs, bashar